Potret Sebagai Data Pribadi Yang Di Komersilkan - Desyanti Suka Asih K.Tus. (Jurnal Ilmiah Raad Kertha, 2019)
Portraitis works of copyrighted photography with human objects. Personal data is data inthe form of personal identities, codes, symbols, letters or numbers of personal identifiers.Personal data includes personal life affairs including (history) someone's communication.Whereas in concept, personal data is not merely information about domestic sphere, but alsoinformation about professional history,professional and public life because a person'spersonal affairs also intersect with the relevant public affairs (interpesonal relationships andalso facts that occur in public spaces). Legitimacy of personal rights is regulated asconstitutional rights as regulated in Article 28G paragraph (1) of the 1945 Constitution ofthe Republic of Indonesia. Portrait in which there are human beings as objects is part ofpersonal data. Portrait is part of human identity that must be protected. The use of unlicensedportraits for commercial purposes can be detrimental to portrait owners not onlyeconomically, this action injures self-identity which can cause a bad image for that person.The use of portraits as personal data without permission for commercial purposes can besubject to criminal sanctions (Copyrights Law) and civil claims (Law on ElectronicInformation and Transactions). This paper discusses how portrait settings are as commercialdata. The purpose of this writing is that the output of the purpose of this paper is as the outputof the Beginner Lecturer Research compiled by the author with the title "CopyrightProtection on Portrait Photographs in Social Media".